Pengaruh E-Wom Dan Persepsi Nilai Terhadap Keputusan Konsumen Untuk Berbelanja Produk Fashion Secara Online Di Shopee (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Ach. Efendi; Yustina Chrismardani (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to determine the effect of e-wom and perceived value on consumer decisions to shop online at Shopee on fashion products for students of the Faculty of Economics and Business, Trunojoyo University, Madura in 2017 to 2020. The sampling of this study used purposive sampling with a total of 100 respondents. , with data analysis techniques using multiple linear analysis.The results of this study are: 1) E-wom influences consumer decisions to shop online at Shopee on study fashion products to students of the Faculty of Economics and Business, University of Trunojoyo Madura (2) Perception of value affects consumer decisions to shop online at Shopee on fashion products. study at the students of the Faculty of Economics and Business, University of Trunojoyo Madura.